Multigenerational inspections of environmental thermal perturbations promote metabolic trade-offs in developmental stages of tropical fish. (1st September 2022) - Wang, Min-Chen; Furukawa, Fumiya; Wang, Ching-Wei; Peng, Hui-Wen; Lin, Ching-Chun; Lin, Tzu-Hao; Tseng, Yung-Che
Abstract: Global warming both reduces global temperature variance and increases the frequency of extreme weather events. In response to these ambient perturbations, animals may be subject to trans- or intra-generational phenotype modifications that help to maintain homeostasis and fitness. Here, we show how temperature-associated transgenerational plasticity in tilapia affects metabolic trade-offs during developmental stages under a global warming scenario. Tropical tilapia reared at a stable temperature of 27 °C for a decade were divided into two temperature-experience groups for four generations of breeding. Each generation of one group was exposed to a single 15 °C cold-shock experience during its lifetime (cold-experienced CE group), and the other group was kept stably at 27 °C throughout their lifetimes (cold-naïve CN group). The offspring at early life stages from the CE and CN tilapia were then assessed by metabolomics-based profiling, and the results implied that parental cold-experience might affect energy provision during reproduction. Furthermore, at early life stages, progeny may be endowed with metabolic traits that help the animals cope with ambient temperature perturbations. This study also applied the feature rescaling and Uniform Manifold Approximation and Projection (UMAP) to visualize metabolic dynamics, and the result could effectively decompose the complex omic-based datasets to represent the energy trade-off variability. For example, the carbohydrate to free amino acid conversion and enhanced compensatory features appeared to be hypothermic-responsive traits. These multigenerational metabolic effects suggest that the tropical ectothermic tilapia may exhibit transgenerational phenotype plasticity, which could optimize energy allocation under ambient temperature challenges. Knowledge about such metabolism-related transgenerational plasticity effects in ectothermic aquatic species may allow us to better predict how adaptive mechanisms will affect fish populations in a climate with narrow temperature variation and frequent extreme weather events. Graphical abstract: Image 1 Highlights: Thermal experiences promote the metabolic trade-off in early life stages of tilapia. Metabolites organization allows transgenerational adaptations to temperature variation. The machine learning-based visualization benefits metabolomics dynamics analysis.